Social inequity and cervical cancer mortality in Brazil: An integrative review (Research, Society and Development, 2025)
Cervical Cancer (CC) is one of the main causes of mortality among women in Brazil. However, despite the importance of screening and appropriate treatment, access to qualified health services is limited for women living in poverty. This study aims to analyze the scientific evidence on social inequality and mortality from CC in Brazil. The methodology used was an integrative literature review based on articles published between 2020 and 2025. These were analyzed using the MEDLINE, PubMed, and SciELO databases. CC causes 311,000 deaths annually, with 90% occurring in low- and middle-income countries. In Brazil, the North and Northeast regions have a higher incidence, especially among black women with low levels of education. Despite the importance of screening, there are challenges such as late diagnosis and lack of continuity of treatment, reinforcing the need to expand access and reduce social and structural inequalities in women's health care. Therefore, the study highlights socioeconomic inequalities as a significant factor in the incidence of and mortality from CC in Brazil, especially among lowincome women, concentrated in the North and Northeast regions.